CAPITALISM AND SOCIALISM AS IDEOLOGICAL CONSTRUCTIONS IN AMERICAN DYSTOPIAN NOVELS - Anna Sriastuti; Ida Rochani Adi; Muh. Arif Rokhman (Rubikon : Journal of Transnational American Studies, 2021)
Literature reflects the history of people's lives, which includes lifestyle, culture, language, desires, and important events in people's lives. Dystopia novels cannot be separated from discussions about authoritarian government, restraints on people's freedom, criticism of the development of technology and information, exploitation and the class system, and the arbitrariness of the rulers. Despite telling a bad world, Dystopian novels proved popular in America, a country that promised freedom, equality, and freedom to its citizens. The possibility of different realities captured by American popular novelists who differ from their imaginations gave birth to dystopian novels that are popular in American society. Thus, this study is important to analyse Capitalism and Socialism as ideological constructions in American dystopian novels through Fahrenheit 451, The Handmaid’s Tale, Uglies, and The Hunger Games. This research will formulate an understanding of whether or not American dystopian novels confirm or negate the ideology of Capitalism and the ideology of Socialism.